Christa Kilian-Hatz: Khwe Dictionary - Chebanne, Andy (Lexikos, 2007)
Before an assessment of this dictionary is made, it is important to place the Khwe language in its historical and social context. Khwe dam (language of the Khwe), as its speakers would prefer to call it, is a Khoisan language belonging to the Southern African Central-Khoisan under the Khoe cluster (Güldemann and Vossen 2000). It is spoken in Northern Botswana and in the Western Capri-vi Strip of Namibia in the Kavango region. As the compiler correctly observes, there are about 10 000 Khwe-speaking people who live in the Caprivi Strip of North-Western Namibia, Angola, Botswana and Zambia, and at Schmidtsdrift, South Africa. As can be expected from a speech community such as the Khwe, who prefer living in small communities, there are dialects within the Khwe dam. In Botswana, the notable varieties are the Buga (Sand Khwe) and the ≤Ani (River Khwe), which exhibit discernable linguistic differences at the lexical and grammatical levels. However, linguists agree, as Kilian-Hatz also indicates, that the Khwe dam dialectal varieties are definitely related and mutually fairly intelligible (cf. Güldemann and Vossen 2000). As a language that has not been elaborately codified, it is difficult to speak about a standard Khwe dam form. Many other social and linguistic activities need to be carried out to resolve the question of standard Khwe dam (cf. WIMSA 2001).